Directing Polymorphism in the Helical Nanofilament Phase. Issue 24 (10th March 2021) - Park, Wongi; Yang, Minyong; Park, Hyewon; Wolska, Joanna M.; Ahn, Hyungju; Shin, Tae Joo; Pociecha, Damian; Gorecka, Ewa; Yoon, Dong Ki
Abstract: Herein, it is reported that the polymorphism in the helical nanofilament (HNF, B4 ) liquid‐crystalline phase depends on the fabrication methods, that is, UV‐driven formation and template‐assisted self‐assembly in the nanoconfined geometry. As a result, uniaxially oriented HNFs with different helical structures were obtained, in which generation of the twisted‐ribbon and cylindrical‐ribbon polymorphs showed that even the molecular lattice has a different orientation. The detailed structures were directly observed by SEM and grazing‐incidence X‐ray diffraction with synchrotron radiation. The resultant polymorphs could be used in chiro‐optical applications due to the capability for fine control of the helical structures. Abstract : Morphogenesis control : the morphogenesis of the helical nanofilament (HNF) liquid‐crystal phase was controlled to give structures that depend on the growth conditions. Two different growth methods were used to investigate the polymorphism of HNFs: nanoconfinement and light‐driven orientation. This is apparently the first report on the polymorphism of an HNF phase formed by single kind of molecules.